Analysis of Referral Marketing and Trust Icon Corporate Towards Purchasing Decision (Survey Of Consumers of CV Jati Mandiri Company) - Riza Rifathan; Komariah's Woman; Faizal Noble (Khazanah Sosial, 2025)
The phenomenon and research gap in this study is the increasing competition in the manufacturing industry, particularly in the production of truck beds and dump trucks, which requires companies to continuously innovate in their marketing strategies to maintain and enhance customer loyalty. Although referral marketing has been recognized as an effective strategy, its implementation is often not integrated with elements of corporate trust, such as the corporate trust icon. This poses a challenge for companies in creating sustainable customer trust. As a leading company in the manufacturing of truck bodies and dump trucks, CV. Jati Mandiri realizes the importance of innovative marketing strategies to maintain competitiveness. This company demonstrates a commitment to implementing referral marketing combined with a corporate trust icon that reflects credibility and professionalism. Is there an influence of referral marketing on purchasing decisions at CV. Jati Mandiri? Is there an influence of a corporate trust icon on purchasing decisions at CV. Jati Mandiri? Is there an influence of referral marketing and a corporate trust icon on purchasing decisions? This study uses two independent variables (Independent Variables), namely referral marketing (X1) and corporate trust icon (X2) and a dependent variable (Dependent Variable), namely purchasing decision (Y). In this study, the number of respondents is 182. The results of this study are that Referral Marketing has been proven to have a positive and significant influence on the Purchasing Decision of CV. Jati Mandiri consumers. The Corporate Trust Icon has also been proven to significantly influence the Purchasing Decision made by CV. Jati Mandiri consumers. Simultaneously, both variables, namely Referral Marketing and Corporate Trust Icon, have a large contribution and complement each other in influencing the Purchasing Decision of CV. Jati Mandiri consumers.